“Kapit sa Patalim”: Social Stratification and Social Realism in Gloc-9’s Select Lyrical Poems - Cortes, Camille P.; Gamao, Liezel B.; Sollano, Julie Ann R.; Mangompit, Rowanne Marie M. (RIRAI Publisher, 2024)
The Philippines is a country that values music tremendously. Filipino composers create music that reflects the passions that drive political and social awareness in the Philippines. Serving as a voice for every citizen who is a victim of society and demonstrating the importance of music as a transforming force for national awareness, Filipino songwriters make songs reflecting the challenges of every Filipino. Music is a tool for political and social criticism. It is a means of addressing social injustice. In Aristotle Pollisco's (Gloc-9) five select lyrical poems, this study distinguished the expressions of the Filipinos' struggle with social class and difficulties of the working people. Gloc-9 uses music to depict the challenges of Filipinos, highlighting delinquency, criminality, societal, and political issues, and how parents must scrimp and save to send their children to school and provide them with a bright future. This research focused on Filipinos and their unwavering tenacity in the face of societal challenges. It would delve more into how Aristotle Pollisco, better known by his stage name as Gloc-9, uses music to express these issues. This research attempted to bring Gloc-9 to the Gen-Zs (12-24 years old) whose musical tastes have shifted towards Westernized themes, which are improper and irrelevant to their age.